Analysis of Recent Mine Blasting Accidents - Larry R. Fletcher (International Society of Explosives Engineers, 1983)
The Bureau of Mines obtained blasting accident data from the Mine Safety ant Health Administration (MSHA), U. S. Department of Labor. These data were analyzed to determine the most frequent causes of accidents in mine blasting. Accident totals for 1971 through 1981 are tabulated for metal-nonmetal and coal mines both surface and underground. In the past 11 years (1971-1981, inclusive) there has been an annual average of 9 fatal and 121 nonfatal blasting accident victims. Underground mining averaged 6 fatal and 93 nonfatal injuries each year.